Laparoscopic treatment of ovarian granulosa cells tumor developed in the pelvic anterior preperitoneal space 20 years after laparotomic salpingo-oophorectomy: case report and review of literature. (2nd October 2020) - Tinelli, Raffaele; Stomati, Massimo; Trojano, Giuseppe; Uccella, Stefano; Cosentino, Francesco; Cicinelli, Ettore; Angioni, Stefano
Abstract: Granulosa cells (GC) tumors are rare tumors which account for approximately 2–3% of all ovarian malignancies with a favorable prognosis. We report a case of a 54-year-old postmenopausal woman who developed an ovarian GC tumor in the pelvic anterior preperitoneal space 20 years after laparotomic salpingo-oophorectomy due to small part of the cyst could drop or remain entrapped into the abdominal wound during the closure of laparotomy 20 years before. Then, the patient underwent a second laparoscopic procedure with peritoneal washing, a type A radical hysterectomy, omentectomy, appendectomy, and pelvic and para-aortic lymphadenectomy. This rare case of ovarian GC tumor developing in the site of previous laparotomy demonstrates the importance of a correct and clean surgical procedure to avoid the risk of leaving even small portions of the cyst exposing the patients to either the risk of malignancy or additional surgical procedures. Precis: This rare case of ovarian granulosa cells tumor developed from residual ovarian tissue intrapped into the abdominal wound 20 years after laparotomic ovariectomy.